PRODUK EKSPOR PROSPEKTIF INDONESIA KE PERU DAN FAKTOR-FAKTOR PENENTU ALIRAN PERDAGANGANNYA KE KAWASAN AMERIKA SELATAN - Dewi Setyawati; Rina Oktaviani; Tanti Novianti (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2014)
Peru in South America area has potential market for Indonesia’s products and has been established as prospective market. This study is aimed to analyze the performance of bilateral trading between Indonesia and Peru, to analyze the export products prospective for Indonesia-Peru bilateral trading and also the factors affecting its trade flow to South America. The analysis methods used in this research were Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), Intra Industry Trade (IIT) and gravity model. Gravity model used panel data with modification sample cross section data of South America countries (Peru, Argentina, Brazil, Chili, Ecuador, Colombia, Paraguay, Suriname, Uruguay and Venezuela) from 2000-2013 time series. The result showed that trade balance as indicator of performance in bilateral trading Indonesia-Peru have been increasing. Indonesia’s export product prospective to Peru are HS 4001 (Natural rubber, balata, gutta-percha etc), HS 0801 (Brazil nuts, cashew nuts & coconuts), HS 5509 (Yarn of synth staple fibre, not put for retail sale), and HS 4420 (Wood marquetry & inlaid wood; caskets & cases or cutlery of wood). Only HS 5509 (Yarn of synth staple fibre,not put for retail sale) and HS 0801 (Brazil nuts, cashew nuts & coconuts) have weak integration. The gravity model with Fixed Effect Model showed that different GDP per capita and trade/GDP have significant positive effect on value export of product prospective. Tariff have significant negative effect for HS 0801 (Brazil nuts, cashew nuts & coconuts), HS 5509 (Yarn of synth staple fibre,not put for retail sale) dan HS 4420 (Wood marquetry & inlaid wood; caskets & cases or cutlery of wood). Economic distances have significant negative effect exclude HS 4001 (Natural rubber, balata, gutta-percha etc). Real exchange rate have significant possitive only for HS 5509 (Yarn of synth staple fibre,not put for retail sale), while the others product have not significant effect. Keywords : Indonesia-Peru-South America Trading, RCA, EPD, IIT, Gravity model